Advanced exergy analysis for a bottoming organic rankine cycle coupled to an internal combustion engine. (15th October 2016) - Galindo, J.; Ruiz, S.; Dolz, V.; Royo-Pascual, L.
Highlights: Advanced exergy analysis were carried out using experimental data of an ORC. Exergy destruction analyzed as endogenous/exogenous and unavoidable/avoidable. Exergy destruction was estimated by considering technological restrictions. Abstract: This paper deals with the evaluation and analysis of a bottoming ORC cycle coupled to an IC engine by means of conventional and advanced exergy analysis. Using experimental data of an ORC coupled to a 2 l turbocharged engine, both conventional and advanced exergy analysis are carried out. Splitting the exergy in the advanced exergy analysis into unavoidable and avoidable provides a measure of the potential of improving the efficiency of this component. On the other hand, splitting the exergy into endogenous and exogenous provides information between interactions among system components. The result of this study shows that there is a high potential of improvement in this type of cycles. Although, from the conventional analysis, the exergy destruction rate of boiler is greater than the one of the expander, condenser and pump, the advanced exergy analysis suggests that the first priority of improvement should be given to the expander, followed by the pump, the condenser and the boiler. A total amount of 3.75 kW (36.5%) of exergy destruction rate could be lowered, taking account that only the avoidable part of the exergy destruction rate can be reduced.